2022
DOI: 10.1021/acs.jpcc.2c02749
|View full text |Cite
|
Sign up to set email alerts
|

Sc-B24N24: A New Low-Density Allotrope of BN

Abstract: Like atoms, nanoclusters can also serve as building blocks for new materials. Here, based on the synthesized cagelike B24N24 clusters, we establish a new sp3-hybridized BN allotrope, termed as sc-B24N24. The geometry, stability, equation of state, mechanical properties, and electronic and optical properties of this superatomic structure are systematically investigated using first-principles calculations. The results reveal that sc-B24N24 is energetically, dynamically, and mechanically stable. The analysis of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The similar valance electronic configuration between the B-N bond and the C-C bond makes boron nitrides have many polymorphs, similar to carbon, including zero-dimensional (0D) clusters, one-dimensional (1D) nanotubes and nanoribbons, two-dimensional (2D) nanosheets, and three-dimensional (3D) crystalline or amorphous BN [ 1 , 2 , 3 , 4 , 5 ]. As a new level of material structure, the study of clusters is helpful to understand the evolution law of matter from microscopic atoms and molecules to macroscopic condensed matter; it also provides an ideal platform to explore the novel physic phenomena of the 0D nano-system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar valance electronic configuration between the B-N bond and the C-C bond makes boron nitrides have many polymorphs, similar to carbon, including zero-dimensional (0D) clusters, one-dimensional (1D) nanotubes and nanoribbons, two-dimensional (2D) nanosheets, and three-dimensional (3D) crystalline or amorphous BN [ 1 , 2 , 3 , 4 , 5 ]. As a new level of material structure, the study of clusters is helpful to understand the evolution law of matter from microscopic atoms and molecules to macroscopic condensed matter; it also provides an ideal platform to explore the novel physic phenomena of the 0D nano-system.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the electronic and optical properties showed that sc-B 24 N 24 was a semiconductor. Remarkably, if the sc-B 24 N 24 framework was taken as the host for endohedral doping of magnetic impurities, a desirable magnetic material was obtained, which exhibited a ferromagnetic (FM) half-metallic ground state with complete spin polarization [ 5 ]. In all these reported BN cluster-assembled phases, the clusters could maintain their structural characteristics when interacting with neighboring clusters.…”
Section: Introductionmentioning
confidence: 99%